Fiscal policy and the recession: The case of Greece - Ersi Athanassiou (Intereconomics, 2009)
This paper presents an analysis of the implications of Greece's intense and long-lasting fi scal and external imbalances for the potential efficacy of a discretionary fiscal policy response to the current recession. It argues that, given recent developments in interest rate spreads and the credit markets' increased sensitivity to risk, the interest rates applicable to the entire amount of Greece's external debt would tend to be higher with a fiscal expansion than without one. Moreover, it deduces from a simple model that the leakages associated with increased interest payments to foreign creditors could well cancel out any positive multiplier effects generated by a fi scal expansion, resulting in a failure to stimulate growth. The implications of this finding for policy is that Greece should continue to avoid the adoption of a fi scal stimulus package, not only out of respect to its fiscal obligations as an EU member but, ultimately, because such a package would be ineffective as an economic recovery tool. While the analysis focuses on the Greek economy, it may be of relevance to other EU economies suffering from serious macroeconomic imbalances.
Keywords: 330